2015
DOI: 10.3390/hydrology2020093
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration Trends Over the Eastern United States During the 20th Century

Abstract: Most models evaluated by the Intergovernmental Panel for Climate change estimate projected increases in temperature and precipitation with rising atmospheric CO2 levels. Researchers have suggested that increases in CO2 and associated increases in temperature and precipitation may stimulate vegetation growth and increase evapotranspiration (ET), which acts as a cooling mechanism, and on a global scale, may OPEN ACCESSHydrology 2015, 2 94 slow the climate-warming trend. This hypothesis has been modeled under inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
(74 reference statements)
1
32
0
1
Order By: Relevance
“…20 According to this study the effect of increased vegetation activity on E 0v is of a similar magnitude as the effect of changes in the atmospheric conditions. A strong influence of changes in vegetation activity on E was also suggested for the eastern US based on correlations between NDVI and E wb (Kramer et al, 2015). Using simulations from a coupled biosphere-atmosphere model, Bounoua et al (2000) found an E increase of 43 mm y −1…”
Section: Drivers Of the Observed Changes In Catchment Evapotranspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…20 According to this study the effect of increased vegetation activity on E 0v is of a similar magnitude as the effect of changes in the atmospheric conditions. A strong influence of changes in vegetation activity on E was also suggested for the eastern US based on correlations between NDVI and E wb (Kramer et al, 2015). Using simulations from a coupled biosphere-atmosphere model, Bounoua et al (2000) found an E increase of 43 mm y −1…”
Section: Drivers Of the Observed Changes In Catchment Evapotranspirationmentioning
confidence: 99%
“…Those 30 studies that exist generally found increases in E wb in the 20 th century. Examples include large river basins in the US (Milly and Dunne, 2001;Walter et al, 2004;Kramer et al, 2015), the Tibetan Plateau (Zhang et al, 2007), and catchments in Switzerland (Spreafico et al, 2007). A study of 109 basins around the world for the period 1961-1999 found only few significant trends but a tendency towards positive trends in North and South America and Europe and a tendency towards negative trends in Africa and Siberia (Ukkola and Prentice, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, groundwater storage changes are not accounted for in the water balance. Trends in groundwater levels are difficult to quantify, and the evidence is mixed in the study region (Brutsaert, ; Dudley & Hodgkins, ; Kramer et al, ; Shanley, Chalmers, Mack, Smith, & Harte, ), but on balance groundwater levels appear to be lowering over the time period we examined. Nonetheless, the effects of the exclusion of groundwater estimates on the results of any water balance analysis deserve consideration (Sharma & Walter, ).…”
Section: Discussionmentioning
confidence: 92%
“…At a smaller spatial scale in eastern Pennsylvania, a 44‐year analysis of a single 7‐km 2 mixed agricultural‐forest watershed also showed a strong increasing AET trend (Lu et al, ), which was attributed mostly to increased temperatures and a longer growing season. Kramer et al () found an increase in AET across most eastern U.S. hydrologic regions, which they attributed in part to increased transpiration during longer growing seasons. Some models and global‐scale studies have predicted declines in AET, or smaller gains than would be expected from climate drivers alone, associated with increased water use efficiency as stomatal conductance is reduced in response to increasing atmospheric CO 2 concentrations (Mao et al, ; Milly & Dunne, ; Szilagyi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Kramer ve ark. [10], Amerika'nın doğusunda 20. yüzyıl boyunca evapotranspirasyon için artış trendi belirlemişlerdir. Saplıoğlu [11], iklim değişimi araştırmalarında kullanılan trend analizi için yeni bir yöntem geliştirmiş ve geliştirdiği yöntemi Isparta ve Burdur illerinin yağış verilerine uygulamıştır.…”
Section: Introductionunclassified